INTERPRETATION OF CONTRACTS AND "COMMERCIAL COMMON SENSE": DO NOT OVERPLAY THIS USEFUL CRITERION. (12th December 2016) - Andrews, Neil
Abstract : We are there to oil the wheels of commerce, not to put spanners in the works, or even grit in the oil.